Strategi Pemenangan Pasangan Muhammad Natsir dan Wakilnya Joko Sutanto pada Pemilukada Kabupaten Demak Tahun 2015 - Jatmiko, Mohamad Givanandra; Taufiq, Ahmad - (Journal of Politic and Government Studies, 2020)
On December 9, 2015, Demak Regency has held a live Regency head election, the election was followed by three candidates for the Regency head. Two of the prospective spouses are incumbents. Of course, each candidate has different winning strategies. The winning strategy in this study is the plan and objective of Muhammad Natsir and Joko Sutanto to achieve victory in the election of regents in Demak Regency. The formulation of thisresearch problem is: (1) What is the political communication strategy used by Joko Sutanto and his deputy Joko Sutanto at the 2015 Demak Regency Election? (2) The winning factors used by Muhammad Natsir and his deputy Joko Sutanto in the 2015 Demak Regency Election? The research method used in this study is qualitatively descriptive. The research site is in Demak Regency. The type of data used is primary data through interviews with the Campaign Coordinator, Vice Regent Candidate Joko Sutanto and secondary data obtained through winning team documents, KPUD Demak documents, websites, and journals. Data collection techniques using interview and documentation techniques. The results of this study show that the winning strategy of Muhammad Natsir and Joko Sutanto is political communication. Political communication strategies include political rhetoric, political propaganda, political lobbying and campaigning. The step of carrying out communication strategies is to maintain robustness, strengthen political institutions, create togetherness and build consensus. Then, there are several factors that influence the pair of Muhammad Natsir and Joko Sutanto so as to defeat the incumbent pair , those factors are strategy, party coalition, candidate determination, program mission vision, winning team coordination, mass base of supporters, target voters and campaign. Political communication strategy and supporting factors of victory is the strength of muhammad natsir and joko sutanto against two incumbent candidates. It was proven that muhammad natsir and Joko Sutanto were able to achieve a strong victory in all sub-Regencys in Demak Regency which numbered 14 sub-Regencys, with 309,251 votes out of 569,885 valid votes.